Extrachromosomal Circular DNA: A New Target in Cancer - Wu, Pan; Liu, Yuhang; Zhou, Ruijia; Liu, Lingyun; Zeng, Hongli; Xiong, Fang; Zhang, Shanshan; Gong, Zhaojian; Zhang, Wenling; Guo, Can; Wang, Fuyan; Zhou, Ming; et al. (Frontiers in Oncology, 2022)
Genomic instability and amplification are intrinsically important traits determining the development and heterogeneity of tumors. The role of extrachromosomal circular DNA (eccDNA) in tumors has recently been highlighted. EccDNAs are unique genetic materials located off the chromosomal DNA. They have been detected in a variety of tumors. This review analyzes the mechanisms involved in the formation of eccDNAs and their genetic characteristics. In addition, the high-copy number and transcriptional levels of oncogenes located in eccDNA molecules contribute to the acceleration of tumor evolution and drug resistance and drive the development of genetic heterogeneity. Understanding the specific genomic forms of eccDNAs and characterizing their potential functions will provide new strategies for tumor therapy. Further research may yield new targets and molecular markers for the early diagnosis and treatment of human cancer.